2019
DOI: 10.1177/2151459319876859
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Periprosthetic Femoral Fractures Vancouver Type B2: Revision Arthroplasty Versus Open Reduction and Internal Fixation With Locking Compression Plate

Abstract: Introduction:The Vancouver algorithm recommends revision arthroplasty (RA) for Vancouver type B2 (VTB2) fractures. However, open reduction and internal fixation (ORIF) using locking compression plates (LCP) may be a valid and less invasive alternative treatment.Materials and Methods:Between January 2007 and March 2017, we retrospectively recruited all patients treated with either ORIF with LCP or RA for VTB2 fractures in our clinic. All of the following were reviewed: the length of hospital stay, the operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 35 publications
1
50
1
1
Order By: Relevance
“…Our systematic search identified 14 original studies that included patients treated with ORIF and patients treated with revision arthroplasty in the treatment of B2 and B3 PFF [5,16,[19][20][21][22][23][24][25][26][27][30][31][32]. The publications were mainly retrospective cohort studies which did not describe the treatment allocation, provided little information about potential predictive factors and presented diverse outcome parameters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our systematic search identified 14 original studies that included patients treated with ORIF and patients treated with revision arthroplasty in the treatment of B2 and B3 PFF [5,16,[19][20][21][22][23][24][25][26][27][30][31][32]. The publications were mainly retrospective cohort studies which did not describe the treatment allocation, provided little information about potential predictive factors and presented diverse outcome parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The conception that ORIF could be advantageous in PFF around certain loose stems is supported by several reports where ORIF was compared to stem revision in B2 and/or B3 fractures and resulted in equivalent, if not better, outcomes [5,16,[19][20][21][22][23][24][25][26][27].…”
Section: Current Treatment Recommendations Under Debatementioning
confidence: 99%
See 1 more Smart Citation
“…For example, the one-year mortality after a periprosthetic fracture of the femur is 30%, therefore, conservative treatment should be considered in non-ambulatory patients and patients with severe morbidity and/or low life expectancy. 11 14 Some studies have documented that ORIF resulted in less intraoperative blood loss and shorter operation time than stem revision; 18 , 21 this could also be a reason for a surgeon to favour ORIF over stem revision in patients with poor health and low physical demands, despite stem revision being indicated. These considerations are patient specific and are not incorporated into our algorithm.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 In general, it is accepted that Vancouver B1 fractures can be treated with ORIF, and some newer studies on Vancouver B2 fractures have also found good clinical results following ORIF in selected cases. 18 21 However, most loose stems must be revised. Whether or not a revision is necessary, or whether ORIF alone is sufficient, is not a straightforward decision.…”
Section: Introductionmentioning
confidence: 99%